Fertility and biochemical activity in sodic soils 17 years after reclamation with flue gas desulfurization gypsum - Yong-gan ZHAO; Shu-juan WANG; Jia LIU; Yu-qun ZHUO; Yan LI; Wen-chao ZHANG (Journal of Integrative Agriculture, 2021)
Previous studies have mainly focused on changes in soil physical and chemical properties to evaluate the reclamation of sodic soils using flue gas desulfurization (FGD) gypsum. However, information on the effects of this reclamation method on microbial-based indicators of soil quality is limited, particularly after many years of FGD gypsum application. This study aimed to investigate the long-term effects of FGD gypsum on soil organic carbon (SOC), nutrients, microbial biomass and enzyme activity. Data were collected from soils of three exchangeable sodium percentage (ESP) classes (i.e., low-, middle- and high-ESP classes of 6.1–20, 20–30 and 30–78.4%, respectively) 17 years after FGD gypsum treatment in Inner Mongolia, China. Averaged across the three ESP classes, FGD gypsum application increased the SOC contents at the 0–20 and 20–40-cm soil depths by 18 and 35%, respectively, and increased available potassium at the 0–20-cm soil depth by 51% compared with the no-gypsum controls. The microbial biomass carbon and microbial biomass nitrogen contents at the 20–40-cm soil depth increased by 69 and 194%, respectively, under FGD gypsum. Except in the high-ESP class, urease activities in the 0–40 cm soil profile were significantly higher in the FGD gypsum treatments than in the controls. A significant increase in alkaline phosphatase activity was concentrated in the 20–40 cm soil layer; few classes showed significant increases in catalase and invertase activities in the 0–20 cm soil layer. Pearson correlation analysis showed that increases in soil fertility and biological activity could be attributed to reductions in electrical conductivity, pH and ESP caused by FGD gypsum application. These results confirm that FGD gypsum application is a viable strategy for reclaiming sodic soils due to its positive effects on soil fertility and biochemistry and that it may contribute to soil ecosystem sustainability.